A review of neurocognitive functioning and risk for psychopathology in sex chromosome trisomy (47, XXY, 47, XXX, 47, XYY). Issue 2 (March 2019) - van Rijn, Sophie
Abstract : Purpose of review: About one in 650–1000 children is born with an extra X or Y chromosome, referred to as sex chromosome trisomies (SCTs). Studying SCTs may uncover unique insights in neurodevelopmental pathways underlying the risk for neurobehavioral problems and psychopathology. There is also a clinical need for more knowledge about the phenotype of SCT with the recent introduction of noninvasive prenatal screening. Recent findings: The reviewed studies illustrate an increased vulnerability for psychopathology such as (symptoms of) autism spectrum disorder, attention-deficit/hyperactivity disorder, anxiety, depression and, to a lesser degree, psychotic disorders. Although traditionally the primary focus has been on language and learning problems, recent research suggests that impairments in executive functioning, social cognition and emotion regulation may also be key factors underlying the risk for neurobehavioral problems. Summary: The research field of SCT is in need of a more longitudinal perspective to identify early markers of 'at risk' development, and to assess the effectiveness of early interventions. Neurocognitive markers that signal compromised neurodevelopment may prove to be helpful in this. Variability in the SCT phenotype provides a unique opportunity to identify not only genetic but also environmental factors that shape neurodevelopmental outcome, calling for studies focused on understanding individual differences.